Reveal Culture Siri’ Na Pacce In Regional Financial Management: Case Study on Financial and Asset Management Board of Jeneponto Regency - Ratmadany, Ainun Mardya; Bulutoding, Lince; Suhartono, Suhartono (Politeknik Keuangan Negara STAN, 2023)
Jeneponto Regency has never received a Qualified Opinion until the Regional Government Financial Report for the 2020 fiscal year and has been included in the 3T area, one of the criteria for which is the regional financial capacity. The purpose of this study is to reveal the role of siri' na pacce culture in regional government financial management in Jeneponto Regency and to find out the meaning behind siri' na pacce values ??in regional financial management in the Jeneponto district government. This study uses a qualitative method with a phenomenological approach. The results of this study are that in general the financial management of the Jeneponto district has implemented siri' na pacce which acts as an unwritten rule in the Jeneponto community which then grows into a life principle that is firmly held in carrying out the mandate. Siri' na pacce is seen and interpreted in a varied and broad way depending on the point of view of its use or the circumstances of the use of the culture. The meaning behind the informant's statement found that there are several values ??contained in siri' na pacce, namely: 1) The value of responsibility, this accountability is done to God, humans, and nature. 2) The value of honesty, and 3) The value of self-esteem which in this study is called the siri' na pacce accountability trilogy concept (TASP). In conclusion, this value plays a role in managing regional finances as a reminder and limitation to be able to optimize regional financial management.